Endophytic colonization of tomato plants by the entomopathogenic fungus Beauveria bassiana for controlling the South American tomato pinworm, Tuta absoluta - Ana Carolina Loreti Silva; Gerson Adriano Silva; Pedro Henrique Nogueira Abib; Aline Teixeira Carolino; Richard Ian Samuels (CABI Agriculture and Bioscience)
Abstract Background The deployment of entomopathogenic fungi (EPF) for the control of crop pests is an important alternative to synthetic pesticides. Despite recent advances in EPF formulations and application techniques, their efficacy is still limited by abiotic and biotic factors. Entomopathogenic fungi naturally colonize plant tissues or they can be artificially inoculated, protecting the plants from insect attack. Beauveria bassiana is the most widely used fungal biological control agent and has potential as an endophyte to protect a range of crops. Although B. bassiana is known to be pathogenic to the South American tomato pinworm, Tuta absoluta (Meyrick), this fungus could be more efficient when deployed as an endophyte to protect tomato plants from attack. Methods Three B. bassiana isolates were screened for virulence against T. absoluta larvae by application of conidia to leaf surfaces. Following confirmation of virulence, tomato plants were then exposed to conidial suspensions using a forced uptake technique. Only one isolate, LPP139, colonized the leaves. Seedlings were then inoculated with LPP139 and the presence of the fungus in different plant tissues was monitored over 30 days. Possible effects of B. bassiana endophytic colonization on plant development were also evaluated. Following confirmation of endophytic colonization of leaf tissues, T. absoluta 2nd or 3rd instar larvae were offered leaves and survival was monitored over a 7-day period. Results All three B. bassiana isolates were virulent to T. absoluta, with approximately 90% mortality over 10 days when conidia had been applied to leaf surfaces. Various plant inoculation techniques were tested but only seedling inoculation was successful. LPP139 successfully colonized all of the plant tissues. High percentages of colonization were observed in roots, stems and leaves up to 30 days after inoculation, with no negative effects on plant growth. When T. absoluta larvae were exposed to B. bassiana colonized leaves, survival was reduced to zero over a 7-day period. Conclusions The endophytic colonization of tomato plants with EPF is a promising method of controlling the South American tomato pinworm. The fungus was detectable for up to 30 days, longer than has been previously observed for tomato plants. Seedling inoculation could be a viable commercial option for marketing pre-colonized tomato plants.